Unveiling gender differences: a mixed reality multitasking exploration - Abbas, Safanah; Jeong, Heejin (Frontiers in Virtual Reality, 2024)
While gender differences have been studied in both real and virtual worlds separately, few studies have focused on multitasking in hybrid environments. This study investigated the gender factor in multitasking within a mixed reality environment. Thirty-six participants completed eight experimental conditions to assess their workload, task priority, and hand usage. Two distinct tasks were employed in the experiment: a block-matching task for the physical world, where participants located and matched English letters with their corresponding positions on a wooden board, and the N-back task for the virtual world. Four conditions focused on digital-physical monotasking, while the rest involved mixed-reality multitasking. The results reveal that perceived mental demand is a significant factor. Males prioritized virtual tasks, whereas females prioritized both tasks equally. Understanding the factors influencing gender-based performance differences can enhance the design of practical mixed reality applications, addressing equity and quality concerns. This study suggests that cognitive load plays a vital role in determining how genders perform when juggling multiple tasks, both physical and virtual.